Methylphenidate Toxic Exposure Reports - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Methylphenidate (MPH) exposures reported to a regional poison control center during a 2-year period were analysed at Wayne State University School of Medicine, Detroit, MI.